2011
DOI: 10.1186/1471-2474-12-221
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injections of sodium hyaluronate (Hyalgan®) in osteoarthritis of the knee. a randomized, controlled, double-blind, multicenter trial in the asian population

Abstract: BackgroundThe efficacy and tolerability of 500-730 kDa sodium hyaluronate (Hyalgan®) for treatment of osteoarthritis (OA) pain has been established in clinical trials, but few data are available in the Asian population. We conducted a randomized, double-blind, multicenter, placebo-controlled study to evaluate the efficacy and tolerability of this preparation in a Taiwanese population.MethodsTwo hundred patients with mild to moderate OA of the knee were randomized to receive five weekly intra-articular injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 15 publications
1
79
0
5
Order By: Relevance
“…Our results suggest that maximal benefit occurs at different times following injection with HA and IAS. These results are consistent with prior systematic reviews27 59 60 that found superiority of IAS injection over HA injection from 0 to 4 weeks after administration but that also found that HA injection was superior to IAS from 4 to 26 weeks. In this regard, each injectable medication may have a different role in treating those with knee OA.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that maximal benefit occurs at different times following injection with HA and IAS. These results are consistent with prior systematic reviews27 59 60 that found superiority of IAS injection over HA injection from 0 to 4 weeks after administration but that also found that HA injection was superior to IAS from 4 to 26 weeks. In this regard, each injectable medication may have a different role in treating those with knee OA.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, the 8% capsaicin patch is applied under medical supervision after a topical anesthetic has been applied [73]. Intra-articular injections of hyaluronan or corticosteroids have also demonstrated efficacy for treating OA without causing significant safety concerns [74,75]. Injections of DOI: 10.1080DOI: 10.…”
Section: Topical Preparationsmentioning
confidence: 99%
“…Huang et al found 5 weekly doses of HA improved knee pain and functional status of the affected joint for up to 25 weeks after finishing the treatment course [24], while Foti et al added there are also significant improvements in range of motion and quality of life [25]. Bannuru et al investigated the time course of HA action and found it reached peak efficacy at 4 weeks post-injection and continued to confer benefit for up to 24 weeks duration [26].…”
Section: Viscosupplementationmentioning
confidence: 99%